Edge Toroidal Rotation Analysis by CXRS Diagnostic on EAST. (17th August 2020) - Jiang, D.; Li, Y. Y.; Wu, X. Q.; Zhang, T.; Lyu, B.; Gao, X.; Xu, G. S.
Abstract: Understanding the influence of edge toroidal rotation in confined plasmas on the L-H transition is important for improving the plasma performance of future fusion devices. We report the results of experiments on the Experimental Advanced Superconducting Tokamak (EAST) to study this relationship. We used edge toroidal charge exchange recombination spectroscopy (eCXRS) as a diagnostic to study edge toroidal rotation. By analyzing the contribution of each term in the radial electric field, our experimental results show how the L-H transition depends on the edge toroidal rotation. Generally, the power of the transition increases with increasing edge toroidal rotation. The observed reduction of injected power can be explained by the change of the edge radial electric field. This reduced power threshold at lower toroidal rotation could provide an important benefit for inherently low-rotation plasma devices such as ITER and the China Fusion Engineering Test Reactor (CFETR).